Misi al-Qur'an Dalam Terapi Moral - Shomad, Bukhori Abdul (KALAM, 2017)
This paper examines the "mission of the Qur'an in Moral Therapy" with the focus on the issue: What is the mission of the Qur'an in Giving Moral Therapy? through theoretical contributions, can explore the mission of the Qur'an as a solution to moral therapy, while its practical contribution, as a new academic paradigm in providing solutions to moral decadence in this modern era. The purpose of this study is to identify the mission of the Qur'an in Providing Moral Therapy. Observing the above terms, then the type of research presented is the Library Research means that all data sources required in this study are various materials or papers relevant to this research related to the mission of the Qur'an in moral therapy, using the method of inductive thinking, deductive and comparative. These three methods of scientific thinking are not partially actualized but are implemented in an integrative manner. Furthermore, the resulting research findings are four dimensions of the Qur'an's mission in moral therapy, namely: (1) the dimension of the Qur'an as the ocean of science; (2) the dimension of the Qur'an as the basis of aqidah and sources of law; (3) the dimension of the Qur'an as the basis of motivation and source of value; and (4) the dimension of the Qur'an as a medicine (bidder) various liver diseases.